2020
DOI: 10.1001/jamanetworkopen.2020.15656
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sociodemographic Factors With Immunotherapy Receipt for Metastatic Melanoma in the US

Abstract: Key Points Question Are sociodemographic factors associated with likelihood of receiving immunotherapy for patients diagnosed with metastatic melanoma in the US? Findings In this cohort study of 9512 metastatic melanoma cases diagnosed between 2013 and 2016 in the National Cancer Database, factors associated with receiving immunotherapy included diagnosis in Medicaid expansion states, residence in areas with high rates of high school graduation, and treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 37 publications
0
44
0
Order By: Relevance
“…We and others have previously analyzed ICI use patterns for patients with advanced melanoma primarily in the ipilimumab era, when anti–PD-1 use was likely restricted to clinical trial or off-label use. 2 , 12 , 29 , 30 , 31 Herein we found that first-line ICI use has increased to 63% of newly diagnosed patients with stage IV melanoma in 2019, from 9% in 2010 and 39% in 2015 (the year leading up to FDA approval of first-line anti–PD-1). In order to investigate the patient, socioeconomic, and care setting factors associated with underutilization of first-line ICI, we also incorporated landmark time points into our analysis to help account for the immortal time bias associated with receipt of ICI, in which early mortality would preclude patients who would otherwise receive first-line ICI from doing so.…”
Section: Discussionmentioning
confidence: 90%
“…We and others have previously analyzed ICI use patterns for patients with advanced melanoma primarily in the ipilimumab era, when anti–PD-1 use was likely restricted to clinical trial or off-label use. 2 , 12 , 29 , 30 , 31 Herein we found that first-line ICI use has increased to 63% of newly diagnosed patients with stage IV melanoma in 2019, from 9% in 2010 and 39% in 2015 (the year leading up to FDA approval of first-line anti–PD-1). In order to investigate the patient, socioeconomic, and care setting factors associated with underutilization of first-line ICI, we also incorporated landmark time points into our analysis to help account for the immortal time bias associated with receipt of ICI, in which early mortality would preclude patients who would otherwise receive first-line ICI from doing so.…”
Section: Discussionmentioning
confidence: 90%
“…89 In the case of immunotherapy, there is accumulating evidence documenting barriers in access to immunotherapy from large population-or hospital-based data, cancer registries, and meta-analyses. [55][56][57][90][91][92][93] This constellation of factors can be summarized as patient-, provider-, health care system-, and societal/policy-level factors.…”
Section: Barriers To Equal Access To Immunotherapymentioning
confidence: 99%
“…Insurance-associated differences in immunotherapy use have been previously described, albeit not specifically with regard to the preapproval era. 13 , 25 , 36 , 37 Lower income has been associated with lower use of immunotherapy for melanoma 27 , 38 but not for RCC and NSCLC. One possible explanation could be travel burden because, particularly among patients with RCC and melanoma, fewer than one-half of the hospitals that treated patients for the 3 cancer types included in this study were administering immunotherapy before FDA approval.…”
Section: Discussionmentioning
confidence: 99%